Navigating the 21st Century: The Triangle of Education's Holistic Approach to Spiritual, Entrepreneurial, and Technological Integration - Rudiana, Rudiana (AIM: Journal of Islamic Education Management, 2023)
The aim of this study is to investigate the implementation of the Triangle of Education, a holistic learning framework that integrates spirituality, entrepreneurship, and technology with traditional knowledge. The study examines the transformation of the educational landscape, focusing on its impact on pedagogy, curriculum design, assessment, and resource allocation. Methodologically, the research involves an extensive review of educational literature, analysis of curricular changes in institutions that have adopted the Triangle of Education, and surveys and interviews with educators, students, and stakeholders. The findings reveal that the Triangle of Education presents a paradigm shift in education. It equips students with not only academic knowledge but also moral values, adaptability, and self-reliance. The study underscores the importance of teacher training, curriculum redesign, innovative assessment tools, and resource allocation to ensure the successful implementation of this framework. The research holds promising prospects for the future, as the Triangle of Education has the potential to revolutionize the educational landscape, reduce youth unemployment, and create a workforce capable of innovation and economic contribution. This study contributes to the ongoing discourse on redefining education to meet the evolving demands of the 21st century.Â